Can Local Stress Enhancement Induce Stability in Fracture Processes? Part II: The Shielding Effect - Kjellstadli, Jonas T.; Bering, Eivind; Pradhan, Srutarshi; Hansen, Alex (Frontiers in Physics, 2019)
We use the local load sharing fiber bundle model to demonstrate a shielding effect where strong fibers protect weaker ones. This effect exists due to the local stress enhancement around broken fibers in the local load sharing model, and it is therefore not present in the equal load sharing model. The shielding effect is prominent only after the initial disorder-driven part of the fracture process has finished, and if the fiber bundle has not reached catastrophic failure by this point, then the shielding increases the critical damage of the system, compared to equal load sharing. In this sense, the local stress enhancement may make the fracture process more stable, but at the cost of reduced critical force.